Interartistic relatioships: el libro & el gato by Juan Garcia Ponce: from literature into image - Alfredo Zárate Flores; María José Miranda Delgado; Samantha Ximena Esquivel Gandara (ТОВ «Друкарня Мадрид», 2024)
Meaning that intertextuality is a permanent game about references referencing other texts. This operation means, among other things, that text is itself another text, or at least that a writing is present inside other writings. In this context, we can assume that intertextuality is a process of hyperconstruction of the act of writing, manifesting itself as a direct or disguised reference of one text in another.
Keywords: literature; image